2017
DOI: 10.1101/193318
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Synaptic co-transmission of acetylcholine and GABA regulates hippocampal states

Abstract: SummaryThe basal forebrain cholinergic system is widely assumed to control cortical functions via non-synaptic transmission of a single neurotransmitter, acetylcholine. Yet, using immuneelectron tomographic, molecular anatomical, optogenetic and physiological techniques, we find that mouse hippocampal cholinergic terminals invariably establish synapses and their vesicles dock at synapses only. We demonstrate that these synapses do not co-release but co-transmit GABA and acetylcholine via different vesicles, wh… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 105 publications
0
8
0
Order By: Relevance
“…Here we provide both anatomical and electrophysiological evidence that MS/DBB cholinergic neurons corelease GABA in superficial EC layers. It is very likely that the two neurotransmitters are packed into separate vesicles within the same axonal terminals, as was already shown for the supramamillary nucleus to dentate gyrus projections ( 72 ) and the MS to hippocampus projection ( 74 ). Even more interesting and functionally relevant is the question of if and how signaling via the two coreleased neurotransmitters is regulated.…”
Section: Discussionmentioning
confidence: 58%
See 1 more Smart Citation
“…Here we provide both anatomical and electrophysiological evidence that MS/DBB cholinergic neurons corelease GABA in superficial EC layers. It is very likely that the two neurotransmitters are packed into separate vesicles within the same axonal terminals, as was already shown for the supramamillary nucleus to dentate gyrus projections ( 72 ) and the MS to hippocampus projection ( 74 ). Even more interesting and functionally relevant is the question of if and how signaling via the two coreleased neurotransmitters is regulated.…”
Section: Discussionmentioning
confidence: 58%
“…For example, supramamillary nucleus to dentate gyrus and basal ganglia to lateral habenula projections have the capacity to corelease glutamate and GABA ( 72 , 73 ). More relevant to this study, some basal forebrain cholinergic neurons projecting to the neocortex ( 46 ) and hippocampus ( 74 ) were demonstrated to corelease GABA and ACh. Here we provide both anatomical and electrophysiological evidence that MS/DBB cholinergic neurons corelease GABA in superficial EC layers.…”
Section: Discussionmentioning
confidence: 91%
“…Subtypes of these send projections to cortex and other areas, some co‐express other markers like somatostatin or calretinin (Gritti, Manns, Mainville, & Jones, ; Zaborszky et al., ), whereas a subset (or all?) cholinergic neurons co‐release GABA (Case et al., ; Saunders, Granger et al., ; Takács et al., ). Different cell types are often associated with different functions and tremendous insights has been gained by recording cell type specific activities or conducting cell type specific manipulations in the past.…”
Section: Discussionmentioning
confidence: 99%
“…The septo‐hippocampal pathway is the main source of ACh in the hippocampus (Dannenberg et al., ; Lewis & Shute, ; Nilsson & Björklund, ; Nilsson, Kalén, Rosengren, & Björklund, ; Vandecasteele et al., ), and provides widespread innervation of both principal cells and interneurons (Frotscher & Léránth, ). Contrary to the general view of mixed synaptic and non‐synaptic cholinergic signalling (Vizi & Kiss, ), it has recently been shown that the overwhelming majority of cholinergic terminals may establish synapses (Takács et al., ). More specifically, cholinergic fibres terminate in the stratum oriens of CA1 and CA3 (Matthews, Salvaterra, Crawford, Houser, & Vaughn, ), contacting pyramidal cells (Wainer et al., ), GABAergic interneurons (Leranth & Frotscher, ) and dentate granule cells (Nyakas, Luiten, Spencer, & Traber, ).…”
Section: Basal Forebrain Inputs To the Hippocampus And Cortical Areasmentioning
confidence: 93%
“…These anatomical data thus indicated that ACh is released in a manner described as volume transmission, i.e., ACh is released from the axonal terminals into the extracellular space. This view, however, was recently challenged by Takacs et al ( 2017 ) demonstrating that all hippocampal cholinergic terminals establish synapses, and vesicles dock only at synapses. Nonetheless, ACh release in the hippocampal formation affects multiple cells and cellular compartments, which further contributes to network complexity.…”
Section: Acetylcholine Receptors In the Hippocampal Formationmentioning
confidence: 99%